Eliminating Double Taxation of Income from Cross-Border Services in the Digital Era from the UN Model Perspective - Kukulski, Ziemowit (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
Digitalization challenges international tax law provisions dealing with eliminating double taxation of income from cross-border services. In the paper the following issues are discussed: rules elimination double taxation of income from cross-border services in the pre-digital era from the UN Model perspective as well as the UN Model’s response to challenges related to eliminating double taxation of income from cross-border services in the digital era as well as its possible impact on countries’ tax treaty practice. Rules governing taxation of income from cross-border services adopted by the UN Model in pre-digital era are outdated. This raises a question whether recently adopted provisions dealing with fees for technical services and automated digital services change the reality in that area.